Is low birth weight a risk indicator for congenital cytomegalovirus infection? - Zakyieh Al-Hareth; Fawza Monem; Nagwa Abdel Megiud (Journal of Infection in Developing Countries)
Background: Congenital cytomegalovirus infection is currently the leading cause of congenital infection in 0.2-2.2% of live births worldwide leading to variable serious sequalae. The aim of the study was to determine if low birth weight is an indicator of CMV congenital infection evidenced by detecting CMV-DNA in umbilical cord blood at the time of delivery.